Responses of Biocrust and Associated Soil Bacteria to Novel Climates Are Not Tightly Coupled - Antoninka, Anita; Chuckran, Peter F.; Mau, Rebecca L.; Slate, Mandy L.; Mishler, Brent D.; Oliver, Melvin J.; Coe, Kirsten K.; Stark, Llo R.; Fisher, Kirsten M.; Bowker, Matthew A. (Frontiers in Microbiology, 2022)
Climate change is expanding drylands even as land use practices degrade them. Representing ~40% of Earth’s terrestrial surface, drylands rely on biological soil crusts (biocrusts) for key ecosystem functions including soil stability, biogeochemical cycling, and water capture. Understanding how biocrusts adapt to climate change is critical to understanding how dryland ecosystems will function with altered climate. We investigated the sensitivity of biocrusts to experimentally imposed novel climates to track changes in productivity and stability under both warming and cooling scenarios. We established three common gardens along an elevational-climate gradient on the Colorado Plateau. Mature biocrusts were collected from each site and reciprocally transplanted intact. Over twenty months we monitored visible species composition and cover, chlorophyll a, and the composition of soil bacterial communities using high throughput sequencing. We hypothesized that biocrusts replanted at their home site would show local preference, and biocrusts transplanted to novel environments would maintain higher cover and stability at elevations higher than their origin, compared to at elevations lower than their origin. We expected responses of the visible biocrust cover and soil bacterial components of the biocrust community to be coupled, with later successional taxa showing higher sensitivity to novel environments. Only high elevation sourced biocrusts maintained higher biocrust cover and community stability at their site of origin. Biocrusts from all sources had higher cover and stability in the high elevation garden. Later successional taxa decreased cover in low elevation gardens, suggesting successional reversal with warming. Visible community composition was influenced by both source and transplant environment. In contrast, soil bacterial community composition was not influenced by transplant environments but retained fidelity to the source. Thus, responses of the visible and soil bacterial components of the biocrust community were not coupled. Synthesis: Our results suggest biocrust communities are sensitive to climate change, and loss of species and function can be expected, while associated soil bacteria may be buffered against rapid change.